2018
DOI: 10.1002/qj.3318
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a high‐resolution numerical weather prediction model's simulated clouds using observations from CloudSat, GOES‐13 and in situ aircraft

Abstract: This study aimed to assess tropical cloud properties predicted by Environment and Climate Change Canada's Global Environmental Multiscale (GEM) model when run with the Milbrandt–Yau double‐moment cloud microphysical scheme and one‐way nesting that culminated at a (∼300 km)2 inner domain with 0.25 km horizontal grid spacing. The assessment utilized satellite and in situ data collected during the High Ice Water Content (HIWC) and High Altitude Ice Crystals (HAIC) projects for a mesoscale convective system on 16 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…The model interest indicates an awareness of the storm, although the break in high model interest from 1500 to 1550 UTC suggests that placement and/or horizontal extent of the convective activity was inaccurate. This result is consistent with findings of Qu et al (2018), who found differences between simulated and observed cloud amounts using the Canadian Global Environmental Multiscale model to analyze an MCS near French Guiana on 16 May 2015 during the Cayenne field campaign.…”
Section: Fig 15supporting
confidence: 92%
“…The model interest indicates an awareness of the storm, although the break in high model interest from 1500 to 1550 UTC suggests that placement and/or horizontal extent of the convective activity was inaccurate. This result is consistent with findings of Qu et al (2018), who found differences between simulated and observed cloud amounts using the Canadian Global Environmental Multiscale model to analyze an MCS near French Guiana on 16 May 2015 during the Cayenne field campaign.…”
Section: Fig 15supporting
confidence: 92%
“…18. Fragments of frozen drops were also documented through in situ observations reported by Korolev et al (2004) and Rangno (2008).…”
Section: Droplet Fragmentation/shattering During Freezingmentioning
confidence: 99%
“…In these studies, the conclusions about the HM process were obtained based on the observed association with graupel and columnar ice crystals. Fewer studies attributed observations of high ice concentration to drop shattering (e.g., Koenig 1963Koenig , 1965Braham, 1964;Rangno, 2008;Lawson et al, 2017). Ice-ice collisional fragmentation was identified as a source of SIP in natural clouds by Hobbs and Farber (1972), Takahashi (1993), andSchwarzenboeck et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, and the focus of the present study, large‐eddy simulations, cloud system‐resolving models (CSRMs), and limited‐area numerical weather prediction (NWP) models often use Δ x ≪ 1 km with domains containing well over 10 6 columns (Stevens et al, ; Bretherton and Khairoutdinov, ; Milbrandt et al, ). Their 1D RTMs operate directly on well‐resolved cloud fields and make relatively few, if any, assumptions about subgrid‐scale conditions (Qu et al, ). This approach to modelling radiative transfer is known as the Independent Column Approximation (ICA: e.g.…”
Section: Introductionmentioning
confidence: 99%